Passive method for islanding detection using variational mode decomposition - Thakur A.K.; Singh S.P.; Shukla D.; Singh S.K. (My University, 2025)
As the distributed energy resources penetration level increases, the distribution system operator faces a challenging task of unintentional islanding detection. Besides islanding detection schemes are affected due to the presence of different types of distributed generation systems and smart inverters. The presence of these devices hinders the capability of islanding detection schemes. To mitigate these issues, this study proposes a practical methodology of variational mode decomposition-based energy index for islanding detection. It decomposes the sampled voltage signal at the point of common coupling into four modes/intrinsic mode functions (IMFs). Among these modes/IMFs, the energy index of mode two has been utilised to detect the islanding. It is an entirely intrinsic, adaptive, and variational method. The five bus and practical distribution systems have been modelled using PSCAD/EMTDC software while considering various components' practical aspects. The technique has been tested for the mixed type of distributed generation and various transient events. The test results reveal that the proposed method is capable of discriminating the islanding event from other disturbances. © The Institution of Engineering and Technology 2020.